134 Lancashire objective volume evaluation of leg oedema in heart failure randomized controlled cross-over trials (love-HF artificial intelligence research programme): rationale and methodology. (4th June 2021) - Awad, Reham; Jones, Robert; Assaf, Omar; Abdullah, Abdullah; Seed, Alison; Cassidy, CJ; Howard, Lesley; Wong, Suzanne; Taylor, Rebecca; Cleland, John; Lane, Deirdre; Davis, G; et al.
Abstract : Introduction: In England and Wales, heart failure (HF) was the primary diagnosis for >81, 000 hospital admissions in 2016-17, with a 30-day readmission rate of nearly 20%. The National HF Audit reports that half of these admissions were associated with moderate or severe peripheral oedema. Conventionally, leg oedema is assessed and graded by a healthcare professional (HCP). A serial measurement of weight is an alternative method of assessing water retention at home but this relies on patient compliance.The Heartfelt device uses high-resolution cameras to generate 3D images of the lower legs and calculates volumes with a precision of about 20mLs without the need for active patient input. Linking Artificial Intelligence algorithms may then be applied to inform either the patient or a healthcare professional of appropriate actions. Methods: The Lancashire Objective Volume Evaluation of leg oedema in Heart Failure (LOVE-HF) artificial intelligence research programme consists of two pilot randomised controlled, cross-over trials (each with 30 patients and 30 day assessment periods), a registry and screening log (the latter to permit comparison of baseline characteristics to ensure generalisability). Patients with HF who received IV diuretics (within <6 months) or with peripheral oedema despite receiving at least 80 mg/day of oral furosemide (or equivalent), will be enrolled in LOVE-HF (comparing the Heartfelt device on top of standard care to standard care: figure 1 ) and LOVE-HF-2 (comparing the Heartfelt device to weight monitoring: figure 2 ). The efficacy outcome of interest is 'number of days alive out of hospital'. Secondary outcomes include serious adverse events, quality of life, mental wellbeing, hopelessness scores and HF-symptoms. These vanguard trials will determine the feasibility of data-collection and confirm estimates of event rates that will inform the design of a substantial multi-centre trial (GLOVE-HF- GLobal Objective Volume Evaluation of oedema in Heart Failure) to determine the clinical utility of the Heartfelt device. Conflict of Interest: Heart Failure